PENGURANGAN KADAR KLORIDA DALAM PEMBENTUKAN 3-MCPD MELALUI PROSES CPO WASHING DI UNIT REFINERY INDUSTRI MINYAK GORENG - Putra, Ilham Adijas; Ulia, Hasnah (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2021)
The effectiveness of washing crude palm oil (CPO) with demineralized water at 90 ºC in reducing chloride levels, a key precursor to the formation of carcinogenic 3-MCPD esters, has been evaluated. The washing process, carried out with a capacity of ±50 tons/hour and a 6% water dosage, resulted in a 60% reduction in chloride levels, with a maximum reduction of 75.3% observed on the first day of experimentation. Variability in chloride reduction was influenced by the quality of raw materials and storage methods. However, organic chloride, which is covalently bonded to CPO molecules, could not be removed by this process. The findings indicate the need for additional methods to address organic chloride and improve contaminant removal efficiency in palm oil production.